Motivations for Food Consumption during Specific Eating Occasions in Turkey - Chambers, Delores H.; Phan, Uyen T. X.; Chanadang, Sirichat; Maughan, Curtis; Sanchez, Karolina; Di Donfrancesco, Brizio; Gomez, David; Higa, Federica; Li, Han; Chambers, Edgar, IV; Esen, E. (My University, 2016)
Several studies in different countries have been conducted to investigate factors affecting food choices. The objective of this study was to understand the motivations of specific food and beverage choices for different eating occasions in a typical diet of the Turkish people. A convenience sample of 141 respondents from seven different geographical regions in Turkey completed an online survey questionnaire that included questions about demographic information and details about their latest eating occasion. Respondents reported all of their motivations for choosing each food/beverage item reported for that specific eating occasion. Results indicated that different motivations played different roles in food choices of people in Turkey. Liking was a key characteristic for all eating occasions, but key natural concerns were even more important at breakfast, and need and hunger were more important for a mid-afternoon snack. Lunch involved additional motivations such as Sociability, Variety Seeking, and Social Norms. In addition to Liking, choices of different food groups were also driven by other motivations such as Habits, Convenience, Need and Hunger, Natural Concerns, and Health. This study helped better understand the current dietary patterns of Turkish people as well as the motives underlying their choices of foods and beverages for different meals and snacks. These findings could be useful for dietary campaigns that aim to improve eating behaviors in Turkey.
Citation: Chambers, D., Phan, U. T. X., Chanadang, S., Maughan, C., Sanchez, K., Di Donfrancesco, B., . . . Esen, E. (2016). Motivations for Food Consumption during Specific Eating Occasions in Turkey. Foods, 5(2), 14. doi:10.3390/foods5020039
Keywords: Turkey; Turkish; Motivation; Food Choice; Dietary Behavior; Choice